Conjunctions in some English and Vietnamese newletters: a contrastive analysis . M.A Thesis Linguistics: 60 22 15 - Nguyễn, Thị Hoàng Huế (University of Languages and International Studies, 2017)
It is a fact that English has entirely become an international language on account of its highest effectiveness in communication. In effect, a prevalent phenomenon has been occurring in a great number of countries in the world where millions of people are (...)